Beyond the black box in music streaming: the impact of recommendation systems upon artists. (2nd January 2020) - O'Dair, Marcus; Fry, Andrew
ABSTRACT: As algorithms have emerged as a key site of power in contemporary culture and society, they have been scrutinised by a number of media scholars, variously focusing on their opacity, bias and social implications. There has also been important work calling for a shift of attention away from the algorithms themselves to the actors that control them: the fundamental questions we should be asking of algorithms, after all, concern more than the specifics of code. This paper applies the arguments developed by Gillespie and Bucher to the algorithms utilised by music streaming services – the powerful but opaque curatorial systems that suggest songs to users. Although there has been important work on algorithms in the context of music streaming, this focus on music streaming remains relatively unusual. Even in the context of music streaming algorithms, our approach is also novel, in that we focus not on the possible effects upon users of music streaming platforms – that is, music fans – but, rather, on the possible effects on music creators . What, then, might be the effects upon songwriters and artists of the increasing prevalence of recommendation systems in music streaming?